2020
DOI: 10.3390/ijms21124247
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Autophagy by Protein Kinase C-ε in Breast Cancer Cells

Abstract: Protein kinase C-ε (PKCε), an anti-apoptotic protein, plays critical roles in breast cancer development and progression. Although autophagy is an important survival mechanism, it is not known if PKCε regulates autophagy in breast cancer cells. We have shown that silencing of PKCε by siRNA inhibited basal and starvation-induced autophagy in T47D breast cancer cells as determined by the decrease in LC3-II, increase in p62, and decrease in autophagy puncta both in the presence and absence of bafilomycin A1. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
3
15
1
Order By: Relevance
“…The idea of a possible involvement of PKCε emerges from our recent findings, showing that this substrate contributes to the regulation of the negative crosstalk between EMT and autophagy orchestrated by FGFR2c during early steps of epidermal carcinogenesis [ 8 ]. Our hypothesis is also supported by a recent study, reporting that PKCε signaling can negatively impact on autophagy directly converging on MTOR in breast cancer cells [ 18 ].…”
Section: Introductionsupporting
confidence: 86%
“…The idea of a possible involvement of PKCε emerges from our recent findings, showing that this substrate contributes to the regulation of the negative crosstalk between EMT and autophagy orchestrated by FGFR2c during early steps of epidermal carcinogenesis [ 8 ]. Our hypothesis is also supported by a recent study, reporting that PKCε signaling can negatively impact on autophagy directly converging on MTOR in breast cancer cells [ 18 ].…”
Section: Introductionsupporting
confidence: 86%
“…The two TNBC cell lines (MDA-MB-468 and BT549) were placed in a six-well plate according to their growth conditions, and the growth density was 80–90% on the second day. The complete medium was replaced with calcium- and phosphorus-free EBSS, and the cells were collected for protein extraction after being treated for different time-points (0, 2 and 4 h) ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, although miconazole induced LC3-II expression, ATG5 expression was unaffected. Other studies have also observed no change in the protein expression level of ATG5 in experimentally induced autophagy (27,28). In addition, the activity of ATG5 is reportedly regulated by phosphorylation (29).…”
Section: Discussionmentioning
confidence: 90%